Out of Hospital Bystander CPR Rates in Baltimore City, Maryland, 2020-2022, Compared to State and National Rates: A Preliminary Report - Ventura CAI; Lawner BJ; Guyther JE; Gullion J (Open Access Emergency Medicine, 2024)
Christian Angelo I Ventura,1,2 Benjamin J Lawner,3,4 Jennifer E Guyther,3– 5 Jason Gullion6 1Department of Health, Behavior and Society, Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USA; 2Department of Natural and Physical Sciences, Baltimore City Community College, Baltimore, MD, USA; 3Office of the Medical Director, Baltimore City Fire Department, Baltimore, MD, USA; 4Department of Emergency Medicine, University of Maryland School of Medicine, Baltimore, MD, USA; 5Department of Pediatrics, University of Maryland School of Medicine, Baltimore, MD, USA; 6Office of Quality Improvement, Baltimore City Fire Department, Baltimore, MD, USACorrespondence: Christian Angelo I Ventura, Department of Health, Behavior and Society, Johns Hopkins Bloomberg School of Public Health, Baltimore, MD, USA, Tel +1 (732) 372-2141, Email cventura@bccc.eduAbstract: This preliminary study was a rapid retrospective analysis of out-of-hospital cardiac arrest (OHCA) cases from Baltimore City between January 2020 and December 2022, using data from the Cardiac Arrest Registry to Enhance Survival. Of the 1,282 cases in 2022, 27.4% received bystander CPR compared to 40.7% in Maryland and 40.8% nationwide. These findings suggest individuals experiencing OHCA in Baltimore City are 45% less likely to receive bystander CPR. Despite community education initiatives and dispatch-assisted protocols, the low bystander CPR rate indicates significant barriers to intervention. Addressing these disparities may necessitate a health equity-focused investigation into public awareness, CPR training access, and sociocultural factors.Keywords: out-of-hospital cardiac arrest, cardiopulmonary resuscitation, emergency medical services